Bypass vs Endovascular Therapy of Infrapopliteal Lesions for Critical Limb Ischemia - Honda, Takeshi; Tabuchi, Atsushi; Yunoki, Yasuhiro; Takiuchi, Hiroki; Watanabe, Yoshiko; Furukawa, Hiroshi; Yamasawa, Takahiko; Mimura, Daisuke; Tanemoto, Kazuo; Masaki, Hisao (Japanese Journal of Vascular Surgery, 2013)
Objective: This study was conducted to determine whether to perform endovascular intervention or bypass surgery as a treatment option for critical limb ischemia (CLI) with lesions in the popliteal artery or below. Subjects and Methods: A total of 150 patients (164 limbs) with CLI underwent endovascular intervention or bypass surgery for lesions in the popliteal artery or below at our department between May 1995 and June 2011. Therapeutic outcomes were examined by surgical technique. An indication for endovascular intervention was established with the combination of 1) poor general condition, and 2) a stenotic or occlusive lesion ≤ 5 cm. Results: The bypass group (group B) comprised 119 patients (99 males, 20 females) with 131 affected limbs at 46 to 89 years of age (mean: 70 years). The endovascular intervention group (group E) comprised 31 patients (25 males, 6 females) with 33 affected limbs at 47 to 89 years of age (mean: 72 years). There was no significant difference in patient demography between the two groups. Regarding preoperative complications, hypertension was observed in 54% and 61% of the subjects in groups B and E, respectively, diabetes in 36% and 55%, renal dysfunction in 29% and 58%, ischemic heart disease in 27% and 32%, and cerebrovascular disorder in 18% and 23%; renal dysfunction accounted for a significantly higher percentage in group E. As for early postoperative complications, subjects in group B experienced wound infections (6 patients), hemorrhage (2), thrombosis (2), pneumonia (1), and another complication (1), and those in group E experienced wound infections (1) and another complication (1). The hospital mortality rate was 0.8% (1 patient) for group B and 0% for group E. The 3-year cumulative primary patency rate was 72% for group B and 54% for group E; the rate was significantly higher for group B. The 3-year secondary patency rate was 82% for group B and 60% for group E. The 3-year limb salvage rate was 86% for group B and 82% for group E; there was no significant difference between the two groups. The 5-year survival rate was 57% for group B and 42% for group E; the survival rate was significantly lower for group E. Conclusion: For the study population of CLI patients with lesions in the popliteal artery or below, the patency rate was higher for the bypass group than for the endovascular intervention group, whereas there was no difference in the limb salvage rate. Based on the findings in prognosis for survival, the indication for endovascular intervention at our department is believed to be appropriate.